2023
DOI: 10.5194/tc-17-445-2023
|View full text |Cite
|
Sign up to set email alerts
|

Slowdown of Shirase Glacier, East Antarctica, caused by strengthening alongshore winds

Abstract: Abstract. Around large parts of West Antarctica and in Wilkes Land, East Antarctica, increased wind-forced intrusions of modified Circumpolar Deep Water (mCDW) onto the continental shelf have been associated with mass loss over the last few decades. Despite considerable seasonal variability, observations in 2018 have also confirmed relatively high basal melt rates of up to 16 m a−1 underneath the Shirase ice tongue in Enderby Land, East Antarctica. These high basal melt rates are also caused by intrusions of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…We suggest that the overall thinning of CGIS in the last ~decade, the significant increase in cumulative fracture length after 2017, and lack of pack ice to the north in late February 2022 made CGIS particularly susceptible to both wind 60,61 and sea-surface slope changes associated with the AR. Intriguingly, fast ice surrounded the eastern margin of CGIS as it collapsed, a counterexample to several recent studies showing that ice shelves are generally afforded stability during times of extensive fast ice (or consolidated pack ice) coverage [63][64][65] , with notable exception at Shirase Glacier 33,66 . It also maintained its location and structure through 2022-2023 in the absence of CGIS, perhaps pointing to a future role for fast ice: filling a role in polynya formation in regions where ice shelves used to be.…”
Section: Collapse Driven By Internal Stress and Pre-conditioned Sensi...mentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that the overall thinning of CGIS in the last ~decade, the significant increase in cumulative fracture length after 2017, and lack of pack ice to the north in late February 2022 made CGIS particularly susceptible to both wind 60,61 and sea-surface slope changes associated with the AR. Intriguingly, fast ice surrounded the eastern margin of CGIS as it collapsed, a counterexample to several recent studies showing that ice shelves are generally afforded stability during times of extensive fast ice (or consolidated pack ice) coverage [63][64][65] , with notable exception at Shirase Glacier 33,66 . It also maintained its location and structure through 2022-2023 in the absence of CGIS, perhaps pointing to a future role for fast ice: filling a role in polynya formation in regions where ice shelves used to be.…”
Section: Collapse Driven By Internal Stress and Pre-conditioned Sensi...mentioning
confidence: 99%
“…While most EAIS drainage basins are presently close to steady-state, satellite observations track subtle signs of change 27 . Recent protracted and staged retreats have been observed in EAIS [29][30][31][32][33] , and there is evidence for significant past retreat 34,35 . However, there are no documented cases of EAIS ice shelf collapse.…”
mentioning
confidence: 99%
“…Also in East Antarctica, a major calving of the Shirase Glacier Tongue (SGT) immediately followed a large fast-ice breakup in Lützow-Holm Bay (Aoki, 2017). Miles et al (2023) confirmed the relationship between fluctuations in the seaward extent of the SGT and fast-ice presence/absence, with periods of ice-tongue advance and lengthening being correlated with persistent fast ice and shortening/loss events following sporadic fast-ice breakouts (largely in summer; see also Aoki, 2017). The effect of fast ice in limiting iceberg calving (and dispersal), thereby enabling ice-front advance, is also shown for the Cook Ice Shelf (George V Land) by .…”
Section: Couplings Between Fast Ice and Ice Shelvesmentioning
confidence: 99%
“…Moreover, Gomez-Fell et al (2022) showed that in summer with its lower fast-ice coverage, the Parker Ice Tongue experienced higher velocities (by 11%) compared to winter. Elsewhere, there is little/ no evidence that fast ice plays any substantial role in buttressing the Shirase Glacier (Miles et al, 2023), with Nakamura et al (2010) recording only a minimal (0.8% ± 1.3%) change in ice speed at the grounding line following a partial fast-ice breakout event in 1998, and Nakamura et al (2022) reporting no distinguishable ice-speed change after a subsequent fast-ice breakout in 2017.…”
Section: Couplings Between Fast Ice and Ice Shelvesmentioning
confidence: 99%
“…This is associated with the significant length of the coastline (18.000 km) as well as gaps in our knowledge about the current rates of ice cover change. In particular, this is caused by spatiotemporal changes in the velocity of glaciers, even for relatively small areas (within 100 km 2 ) (Tretyak, 2016;Li et al, 2023;Miles et al, 2023).…”
mentioning
confidence: 99%